2005
DOI: 10.1177/1097184x04268799
|View full text |Cite
|
Sign up to set email alerts
|

Firming the Floppy Penis

Abstract: Studies of manhood neglect the old just as social gerontology avoids theorizing masculinity, but theories of age relations have much to offer to the scholarship of men. Preliminary study of a mass-marketed program of "successful aging" suggests that old men with money to spend can consume images of themselves as young again. The authors analyze both the ageism of such a consumer regimen and its implications for old manhood in the contexts of men's endangered physical health, unequal access to wealth, heterosex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…Another factor contributing to increased sexual activity among older men during the last decade has been the development and widespread availability of prescribed PDE-5 inhibitors designed to reduce or eliminate erectile dysfunction (ED). The portrayal of an aspirational lifestyle within the reach of the''sexy senior''ready to take advantage of a concupiscent female partner with the help of ED medications has saturated mainstream media and also contributed to a marked increase in permissible sexual agency, which is actively espoused by some older men but still rejected or ignored by others (Calasanti & King, 2005;Hughes, 2011;Marshall, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Another factor contributing to increased sexual activity among older men during the last decade has been the development and widespread availability of prescribed PDE-5 inhibitors designed to reduce or eliminate erectile dysfunction (ED). The portrayal of an aspirational lifestyle within the reach of the''sexy senior''ready to take advantage of a concupiscent female partner with the help of ED medications has saturated mainstream media and also contributed to a marked increase in permissible sexual agency, which is actively espoused by some older men but still rejected or ignored by others (Calasanti & King, 2005;Hughes, 2011;Marshall, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…For example, older men's experiences as well as the economic, social, and political power that they wield are portrayed as key features of an idealized masculinity in advertising and magazine articles (Calasanti & King, 2005;Hurd Clarke, Bennett, & Liu, 2014). Thus, representations of older men are associated with power and authority as "a-aged" or vintage (Hearn, 1995, p. 107).…”
Section: Media Portrayals Of Later Life Sexualitymentioning
confidence: 94%
“…The accompanying image depicted a confident, striking older man dressed in a casual blue t-shirt embracing an attractive, younger woman whose demure smile suggested that she was sexually satisfied and romantically contented. Within this advertisement, idealized masculinity in the Third Age was equated with sexual activity and assertiveness even as the medicalization of male aging and the promotion of fears around the loss of testosterone appealed to and reinforced negative stereotypes about older men (Calasanti & King, 2005).…”
Section: Older Men As Healthy and Happymentioning
confidence: 99%
“…While the bulk of the existing research on masculinity ideals in advertisements has ignored age, Calasanti and King (2005) have theorized that marketing campaigns for anti-aging products construct old masculinity in two distinct yet related ways, namely, "playing hard" (p. 10) and "staying hard" (p. 13). The former depiction "emphasizes activities modeled after the experiences of middle-aged, white, middle-class men" (p. 10) as older men "propel themselves into hard play as consumers of expensive sports and travel" (p. 10).…”
Section: Introductionmentioning
confidence: 98%